On the stabilizing behavior of zirconia: A combined experimental and theoretical study - Foschini, C. R.; Treu, O.; Juiz, S. A.; Souza, A. G.; Oliveira, JBL; Longo, Elson [UNESP]; Leite, E. R.; Paskocimas, C. A.; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2004)
Reactive zirconia powder was synthesized by the complexation of zirconium metal from zirconium hydroxide using a solution of 8-hydroxiquinoline. The kinetics of zirconia crystallization was followed by X-ray diffraction, scanning electron microscopy and surface area measured by the nitrogen adsorption/desorption technique. The results indicated that zirconia with a surface area as high as 100 m(2)/g can be obtained by this method after calcination at 500degreesC. Zirconia presents three polymorphic phases (monoclinic, tetragonal and cubic), which are reversibly interconversible. The cluster model Zr4O8 and Z(r)4O(7)(+2) was used for a theoretical study of the stabilization process. The ab initio RHF method was employed with the Gaussian94 program and the total energies and the energy gap of the different phases were calculated and compared with the experimental energy gap. The theoretical results show good reproducibility of the energy gap for zirconia. (C) 2004 Kluwer Academic Publishers.